Peace: The Desire of God - Harry Huebner (اخلاق وحیانی)
To be peacemakers as the Christian scriptures imagine is to participate in the original peace of God’s creation. There is also a tradition within the Christian faith that seeks to lessen the distinction between peace as a goal and peace as a way of life and has sought to view peace as an uncompromising mandate. This tradition holds peace to be a Christian calling, a calling to return to the original peace in the God's creation. While peace is never fully embodied on earth, it would be irrelevant if it were not expressible in some measure in time/space existence, and also it would be meaningless to embody it without appealing to the original peace that God has placed in the creation. This account of peace is a shared, fundamental notion in the three monotheistic religions; furthermore it has close relations with the notion of social friendship developed by Aristotle. This is while in the secular, modern society, neither there is any peace in its monotheistic sense nor in its Aristotelian sense of friendship. But the structure of contemporary society could be formed in another way, and making use of peacemaking and deep sources of our religious traditions can help us in doing so.